PEMBELAJARAN KETERAMPILAN BERBICARA BERBASIS TEKS BIOGRAFI PADA KELAS INKLUSI BERDASARKAN KURIKULUM 2013 (STUDI KASUS DI SMAN 8 SURAKARTA) - Gilang Jaka Sanjaya; Muhammad Rohmadi; Purwadi Purwadi (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This research is a case study research. The sampling technique was purposive sampling. Data sources used are events, informants and documents. Data collection techniques are carried out by observation, interviews, and data analysis. Data validity test used is source triangulation, method triangulation, and informant review. The data analysis technique used is an interactive analysis model. The results of this study are descriptions of: (1) RPP components prepared by teachers in accordance with Permendikbud, but the conformity of the contents can not be said either; (2) the implementation of biographical text-based speech-learning in the inclusion class of SMAN 8 Surakarta has been conducted based on the 2013 curriculum; (3) evaluations conducted by subject teachers in the form of giving remedial questions; (4) obstacles faced by Indonesian subject teachers in learning biographical texts at SMAN 8 Surkarta. Teacher constraints include(a) lack of understanding of sign language to communicate with students with special needs for quadriplegic speech; (b) there is no special teacher for ABK; (c) students with special needs tend to close themselves, and (d) lack of use of the media as a medium of learning media. (5) efforts made by Indonesian language teachers at SMAN 8 Surakarta in addressing the problems faced in learning biographical texts in the inclusive class.